Quality improvement of mango chew - Tejas, Ma. Theza Cainglet (2002.)
mango chew formulation developed by Pineda (1999) was modified to improve the sensorial attributes of the chews.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Mango chew; Chew